Foreword (A thousand years of Poland's presence among the elite of European states, 2026)
Ryszard Legutko, the author of the Foreword, uses the millennial anniversary of the coronation of Bolesław the Brave as a starting point for a broader reflection on the process of building and rebuilding the Polish state throughout the centuries.In the body of the text, the author discusses three guiding ideas of the publication. The first is sovereignty — a value that over the course of a thousand years never disappeared from the Polish national consciousness, though today it is threatened by calls for modernization and the transfer of power to supranational structures. The second is constitutionalism — the author traces successive Polish constitutions, from the Constitution of May 3rd to the constitution of the Third Republic, and suggests the need for a new, more stabilizing constitution rooted in the Polish historical experience. The third idea is republicanism, understood as a civic order grounded in virtue and commitment to the common good, whose greatest enemy is deep social division.The author concludes with a call for historical awareness as the foundation of responsible governance. He emphasizes that the Third Polish Republic did not emerge from a vacuum, and that forgetting past experiences condemns Poles to the costly repetition of old mistakes.